Optimizing the synthesis of nanostructured SiO2 from Ethiopian pumice for use in rubber reinforcement - Agraw Mulat Muhammud; Gemechu Deressa Edossa; Fedlu Kedir Sabir (Scientific Reports)
Abstract This study investigated the optimization of synthesis parameters for producing nanostructured SiO2 from Ethiopian pumice for use as rubber reinforcement. Important variables such as pH, sol‒gel synthesis temperature, stirring rate, calcination temperature, sodium silicate modulus, NaOH concentration, and H2SO4 concentration were systematically varied. FTIR, XRD, BET, TGA, and SEM were used to characterize the resulting SiO2 and assess how these parameters affect its morphological, surface, thermal, and structural properties. According to BET analysis, a sodium silicate modulus of 3–4 produced the best results. FTIR and BET tests showed that H2SO4 concentrations of 2 M and 2.5 M were ideal, while NaOH concentrations of 2 M and 3 M were optimal based on BET and XRD analyses. The best silica was obtained within a synthesis temperature range of 70–90 °C, as indicated by XRD, FTIR, and SEM investigations and pH values between 8 and 10 were confirmed by XRD and SEM to be suitable. TGA revealed that the ideal calcination temperature ranged from 600 °C to 800 °C, while SEM showed that the best stirring rate was 600 rpm. These studies confirm that the characteristics of Ethiopian pumice-derived SiO2 for rubber reinforcement are strongly influenced by the optimized synthesis conditions.